(untitled) (Comparative & International Education Series, 2021)
The physical classroom experience holds a complex meaning and role for multilingual international students. In particular, social interaction which occurs within the classroom affords students opportunities to co-construct expert knowledge, acquire and develop linguistic skills, and cultivate cross-cultural and social relationships. This chapter draws on teacher research to explore some of the ways in which the sudden switch to online instruction mid-semester impacted the perceptions of eleven multilingual international students about their academic experiences in a Humanities course at a large Canadian university. The switch to online delivery directly impacted opportunities for meaningful social interaction in the course, and consequently, the students’ overall satisfaction with learning. Additionally, the strong sense of community built through social interaction in the face-to-face classroom was compromised. The findings reinforce the need to prioritise the international student experience in online instruction considering the students’ often unique needs, goals, and expectations. Recommendations around social interaction in online instruction are presented.